Girls of the golden West - Adams, John 1947- (Nonesuch Records Inc., a Warner Music Group Company, 2024)
Girls of the Golden West is a California opera, telling the story of the Gold Rush not through familiar time-worn myth, but in the words and deeds of real people
Keywords: Operas